Preliminary study in the use of electric current for the control of Rhynchophorus ferrugineus - Niamouris, Kostas; Psirofonia, Panagiota (ENTOMOLOGIA HELLENICA, 2014)
The use of electric current is being studied as a method to control Rhynchophorus ferrugineus (Coleoptera: Curculionidae). The infested palm trees were pruned according to the severity of the infestation (heavy infestation requires more intense pruning). Then, electrolytes were injected into the palm trees to elevate conductivity. Electric current of specific voltage and amperage was coursed through the palm trees, using specifically designed electrodes; Electric current was applied for 20 min to 1 hour depending on the severity of the infestation and the size of the palm tree. A small number of palm trees were shocked, some of which were monitored for side effects due to the shock while others were cut down to monitor pest mortality rates. Larvae were collected and placed in entomological cages. A large percentage of larvae were killed after the shock, while the others showed difficulties in their movement. Six days later 84.78 % of larvae and 96.48 % of pupae were killed but practically all of the adults survived. Electric current has never been used in this way to control insects before.